The effect of PhET technology on the achievement of Arabic language teaching methods and the development of personal intelligence among students of Arabic language departments in Colleges of Basic Education (Journal of the College of Basic Education, 2026)
The research aims to: "Identify the effect of the PhET technique on the achievement of the subject of Arabic language teaching methods and the development of personal intelligence among students of Arabic language departments in Colleges of Basic Education." The researcher adopted the experimental method for his study, using an experimental design for two groups (experimental and control). The research population consisted of Colleges of Basic Education, and he selected the College of Basic Education at Al-Mustansiriya University as his research sample, represented by third-year students in the Arabic language department. Classroom (2) was the experimental group with (33) male and female students who studied according to the PhET technique, while classroom (3) was the control group with (33) male and female students who studied using the traditional method. The researcher compared students from both research groups on a number of variables. As for the research tools, the researcher prepared an achievement test post-study according to the test blueprint, consisting of (50) test items, and a personal intelligence scale consisting of (20) items. The researcher verified their validity and reliability and extracted the discrimination indices and difficulty coefficients. The researcher personally taught both research groups throughout the experiment, which lasted a full semester of the academic year (2023-2024). After statistically analyzing the data, the results showed that the students in the experimental group, who were taught the methods of teaching the Arabic language using the PHET strategy, outperformed the students in the control group, who were taught the same material using the traditional method, The researcher also recommended adopting the PhET technology as a modern strategy in teaching the Methods of Teaching Arabic course, as it presents the material in a smooth technological way, and suggested conducting a similar study with other dependent variables for both genders.